LANGUAGE VARIANCES IN DEFINING YOUNG WOMEN IN NORTHERN UGANDA HUMANITARIAN SETTINGS - Namuggala, Victoria Flavia; Kabonesa, Consolata (International Journal of Child, Youth and Family Studies, 2023)
This paper, which focuses on formerly displaced communities in post-conflict northern Uganda, discusses the variance between the way formal institutions view young women’s identities and how young women see themselves. Based on a qualitative study that used in-depth interviews and focus group discussions, findings indicate that the infantilizing and victimizing language adopted by these institutions does not reflect the identities of young women in the post-conflict setting. These women argue that terminology such as “child mother” and “child soldier” is disempowering, denying them the prestige of adulthood yet disassociating them from childhood. The intersecting nature of their perceived identities hinders their access to humanitarian assistance targeted specifically to children or adults, since they are not recognized as clearly belonging to either group. The use of the term “child mother” effectively penalizes young women for engaging in adult (sexual) behaviour, while denying them the adult status that mothers are normally accorded. This article argues that sustainable post-conflict reconstruction, with efficient access to and use of humanitarian assistance, demands insitutional adoption of contextually inclusive language that recognizes young women’s professed identities and is reflective of local experiences and realities.